Classifying Adverse Events Following Lower Limb Orthopaedic Surgery in Children With Cerebral Palsy: Reliability of the Modified Clavien-Dindo System. Issue 10 (November 2018) - Zhou, Leena; Willoughby, Kate; Strobel, Natalie; Thomason, Pam; Gallagher, Charles; Harambasic, Mela; Khot, Abhay; Graham, H. Kerr
Abstract : Background: The modified Clavien-Dindo (MCD) system is a reliable tool for classifying adverse events (AEs) in hip preservation surgery and has since been utilized in studies involving lower limb surgery for ambulant and nonambulant children with cerebral palsy (CP). However, the profile of AEs recorded in children with CP compared with typically developing children is different, and the reliability of the MCD in CP is unknown. This study aimed to evaluate the interrater and intrarater reliability of the MCD system for classifying AEs following lower limb surgery in children with CP. Methods: Eighteen raters were invited to participate, including clinicians from surgical, nursing, and physical therapy professions, and individuals with CP. Following a MCD familiarization session, participants rated 40 clinical scenarios on 2 occasions, 2 weeks apart. Fleiss' κ statistics were used to calculate interrater and intrarater reliability. Results: The overall Fleiss' κ value for interrater reliability in the first rating was 0.70 (95% confidence interval, 0.61-0.80), and increased to 0.75 (95% confidence interval, 0.66-0.84) in the second rating. The average Fleiss' κ value for intrarater reliability was 0.78 (range, 0.48 to 1.00). Grading of more severe AEs (MCD III to V) achieved near perfect agreement (κ, 0.87 to 1.00). There was a lower level of agreement for minor AEs (MCD I-II) (κ, 0.53 to 0.55). A κ score of 0 to 0.2 was deemed as poor, 0.21 to 0.4 as fair, 0.41 to 0.6 as good, 0.61 to 0.8 as very good, and 0.81 to 1.0 as almost perfect agreement. Conclusions: The MCD System demonstrates a very good interrater and intrarater reliability following lower limb surgery in children with CP. The MCD can be used by clinicians from different health care professions with a high level of reliability. The MCD may improve standardization of AE recording with a view to accurate audits and improved clarity in outcome studies for CP. Level of Evidence: Level II—diagnostic. Abstract : Supplemental Digital Content is available in the text.